Pengaruh aktivasi temperatur dan waktu terhadap karakteristik arang aktif dari tandan aren (Arenga longipes mogea) - Siregar, Naudi Hayati; Nabila, Fani Putri; Hasibuan, Ulfa Zahara; Lubis, Yunida Syafriani; Hakim, Luthfi (Universitas Muhammadiyah Mataram, 2025)
Activated charcoal is a porous material with a high pore volume. Sugar palm bunches waste has the potential to be a raw material for the activated charcoal production as an absorbent. This study aims to evaluate the effect of temperature and time activation on activated charcoal from sugar palm bunches. Pyrolysis of sugar palm bunches was conducted at 350-400℃ for 6 hours. The pyrolyzed charcoal was activated using physical method with temperature (575℃ and 625℃) and time (30 and 50 minutes). The characteristics of activated charcoal were evaluated in terms of yield, proximate test, and iodine number. The results from the temperature and time activation showed that the yield of activated charcoal ranged from 79.56 - 82.17%; moisture content of 1.55-8.51%; ash content of 6.63-9.96%; volatile matter of 0.86-1.40%; fixed carbon 83.81-89.59%; as well as iodine number of 841.97-944.44 mg/g, respectively. Statistically, showed that the temperature treatment had a significant effect on all parameters, while the time treatment and the interaction of the both treatments had no significant effect on the yield value, ash content, and iodine number. Based on the quality standards of activated charcoal, all proximate test values and iodine number produced are included in the quality standards of SNI 06-3730-1995.